Analysis of a cooperative dairy producer risk management program - Heiman, Travis (Kansas State University, 2013)
Dairy Farmers of America (DFA) is national milk marketing cooperative. DFA’s primary focus is to market the milk of the cooperative’s 17,000 members. In addition, DFA offers its membership a number of farm services. The sole purpose of these services is to make it easier for DFA members to operate their businesses. One of the services offered provides members access to forward contracting alternatives for pricing their milk. The objective of this research is to utilize demographic and other information related to the characteristics of individual dairy producers and determine how these characteristics impact the use (or lack thereof) of risk management marketing tools. More specifically, the focus of this research is to identify what types of dairy producers are most likely to use the DFA’s forward contracting program. The logit model estimated indicated that regional and demographic differences impact the use of DFA’s forward contracting program. Members in the Mountain Area are most likely to use the program followed by members in the Central Area. Demographic differences that significantly impacted the use of forward contracting include age (older producers use forward contracts less than younger operators) and the size of operation, as measured by milk produced per year (larger operators were more likely to use forward contracting services). While the estimated logit model did identify several factors related to the use of forward contracting services, relationships are not particularly strong and the percent of producers using the services is relatively low. Thus, the model is limited in its ability for identifying key factors and thus it will be difficult for DFA to base a targeted marketing effort at certain producers. DFA would need additional information about their members to successfully target for this farm service.
Keywords: Risk management; Forward contract; Dairy; Cooperative; Agriculture, General (0473); Economics (0501)